Cord blood-derived biologics lead to robust axonal regeneration in benzalkonium chloride-injured mouse corneas by modulating the Il-17 pathway and neuropeptide Y - Ruojing Huang; Caiying Su; Na Zhang; Congying Shi; Guangming Pu; Yong Ding; Wei Wei; Jiansu Chen (BMC, 2024)
Abstract Background Umbilical cord blood-derived therapeutics, such as serum (UCS) and platelet-rich plasma (UCPRP), are popular treatment options in clinical trials and can potentially be utilized to address a clinically unmet need caused by preservatives, specifically benzalkonium chloride (BAK), present in ophthalmic formulations. As current clinical interventions for secondary injuries caused by BAK are suboptimal, this study will explore the feasibility of utilizing UCS and UCPRP for cornea treatment and investigate the underlying mechanisms associated with this approach. Methods Mice's corneas were administered BAK to induce damage. UCS and UCPRP were then utilized to attempt to treat the injuries. Ocular tests were performed on the animals to evaluate recovery, while immunostaining, RNA-seq, and subsequent bioinformatics analysis were conducted to investigate the treatment mechanism. Results BAK administration led to widespread inflammatory responses in the cornea. Subsequent treatment with UCS and UCPRP led to the downregulation of immune-related 'interactions between cytokine receptors' and 'IL-17 signaling' pathways. Although axonal enhancers such as Ngf, Rac2, Robo2, Srgap1, and Rock2 were found to be present in the injured group, robust axonal regeneration was observed only in the UCS and UCPRP treatment groups. Further analysis revealed that, as compared to normal corneas, inflammation was not restored to pre-injury levels post-treatment. Importantly, Neuropeptide Y (Npy) was also involved in regulating immune responses, indicating neuroimmune axis interactions. Conclusions Cord blood-derived therapeutics are feasible options for overcoming the sustained injuries induced by BAK in the cornea. They also have potential applications in areas where axonal regeneration is required.